The Role of Behavioral Planning Interventions in Maintaining Dental and Oral Health Behavior among Students in Yogyakarta, Indonesia - Kusumastiwi, Rr Pipiet Okti; Salsabila Krisnaputri (Open Access Indonesian Journal of Medical Reviews, 2023)
Various efforts and methods have been developed to increase individual awareness of maintaining oral health. Behavioral planning interventions differ from interventions or counseling, which generally only prioritize aspects of knowledge. The theory of planned behavior states that a behavior is not necessarily born from mere knowledge; there are contributions of other factors, such as the role of peer groups and beliefs, which play a role in triggering a behavior. This study aimed to evaluate the role of behavioral planning interventions in maintaining oral health behavior in adolescents. This study is a quasi-experimental study with a pre and post-test design approach. The research was conducted on new students at Universitas Muhammadiyah Yogyakarta, Indonesia. The inclusion criteria for participants were new students (less than six months studying in college), 18 years old, and willing to participate. Participants filled out the initial questionnaire as a pre-test to assess aspects of knowledge related to dental health. Then the subjects were given behavioral planning interventions by creating a group community using social media for all research subjects. The intervention process was carried out for three months. A post-test evaluation was conducted to assess the success of the intervention. Data analysis was carried out using the SPSS version 25 program. The results of this study indicate an improvement in scores related to personal attitude, subjective norms, perceived behavioral control, and behavior to maintain dental and oral health after conducting behavioral planning interventions (p <0.05). In conclusion, behavioral planning interventions help improve individual behavior in maintaining oral health in adolescents.